Self-Control Serves As A Mediating Variable In The Relationship Between Financial Management Behavior And Financial Literacy, Attitudes, And Experience Among STIE Satya Dharma Students. - Sri Ayuni, Ni Made; Komang Rusma Rosita Dewi (Universitas Ibn Khladun Bogor, 2024)
The study's findings demonstrate that among STIE Satya Dharma Singaraja students, financial literacy significantly and favorably influences their money management practices. The way that STIE Satya Dharma Singaraja students manage their finances is positively and significantly impacted by their financial experiences. Self-control is positively and significantly impacted by financial literacy in STIE Satya Dharma Singaraja students. Students' self-control at STIE Satya Dharma Singaraja Students is positively and significantly impacted by their financial views. For STIE Satya Dharma Singaraja students, financial experience has a beneficial and considerable influence on self-control. The money management behavior of STIE Satya Dharma Singaraja students is positively and significantly influenced by their financial views. For STIE Satya Dharma Singaraja students, self-control has a favorable and noteworthy effect on their money management practices. Through self-control, financial literacy has a beneficial and considerable influence on STIE Satya Dharma Singaraja students' money management behavior. Through self-control, financial experience has a beneficial and considerable influence on STIE Satya Dharma Singaraja students' money management behavior.